Effect of chemical production anthropogenic factors on human hepatogenesis - B. L. Ponomaryov; L. Ye. Obukhova; Yu. F. Vysotsky; N. I. Barsukova; T. M. Cherdantseva (Бюллетень сибирской медицины, 2010)
The subjects of the electronic microscopy exploration are hepatogenic features of human embryos and fetuses after exposing pregnant women to harmful substances of chemical industry. Malformation of liver blood capillaries and alteration of structural organization of hepatocytes are identified. Tire manufacturing anthropogenic factors are the reasons of organelle membranes alteration. They affect nuclei of hepatocytes, influence the nuclear chromatin, and decrease cell mitotic activity.